Barriers to Postsecondary Education in Maine: Making College the Obvious and Attainable Next Step for More Maine Students - Quint, Colleen; Plimpton, Lisa (Maine Policy Review, 2002)
The question of why more high school students do not go on to college has been the focus of recent research at the Mitchell Institute. Quint and Plimpton summarize this research, which involved more than 2,500 Maine students, educators and parents. They find that financial barriers are only one piece of a complicated puzzle. Other barriers include parental attitudes, whether any family members have attended college, the high school experience (i.e., what track the student is placed in), the quality of career planning in school and at home, and the level of active planning for college (while many students say they plan to go on to college, some do not take the specific steps necessary to actually do so). By sifting through the layers of what is happening in Maine’s secondary schools and among students and parents, Quint and Plimpton generate a set of practical recommendations for policymakers and educators alike.